Malnourishment affects gene expression along the length of the small intestine - Pinho, Raquel M.; Garas, Lydia C.; Huang, B. Carol; Weimer, Bart C.; Maga, Elizabeth A. (Frontiers in Nutrition, 2022)
Malnourishment is a risk factor for childhood mortality, jeopardizing the health of children by aggravating pneumonia/acute respiratory infections and diarrheal diseases. Malnourishment causes morphophysiological changes resulting in stunting and wasting that have long-lasting consequences such as cognitive deficit and metabolic dysfunction. Using a pig model of malnutrition, the interplay between the phenotypic data displayed by the malnourished animals, the gene expression pattern along the intestinal tract, microbiota composition of the intestinal contents, and hepatic metabolite concentrations from the same animals were correlated using a multi-omics approach. Samples from the duodenum, jejunum, and ileum of malnourished (protein and calorie-restricted diet) and full-fed (no dietary restrictions) piglets were subjected to RNA-seq. Gene co-expression analysis and phenotypic correlations were made with WGCNA, while the integration of transcriptome with microbiota composition and the hepatic metabolite profile was done using mixOmics. Malnourishment caused changes in tissue gene expression that influenced energetic balance, cell proliferation, nutrient absorption, and response to stress. Repression of antioxidant genes, including glutathione peroxidase, in coordination with induction of metal ion transporters corresponded to the hepatic metabolite changes. These data indicate oxidative stress in the intestine of malnourished animals. Furthermore, several of the phenotypes displayed by these animals could be explained by changes in gene expression.